Direct and indirect deforestation for cocoa in the tropical moist forests of Ghana - Cécile Renier; Thomas Addoah; Valentin Guye; Rachael Garrett; Goedele Van den Broeck; Erasmus K H J Zu Ermgassen; Patrick Meyfroidt (Environmental Research: Food Systems)
Across the tropics, cocoa is one of the main drivers of deforestation. In Ghana, the world’s second largest cocoa producer, the role of each of the main economic sectors in driving deforestation remains, however, contested—with cocoa, mining, logging, and plantations each blaming the others. Previous work has also suggested that food crops are displaced into forests by cocoa expansion, raising concerns about indirect land-use change and impacts on food availability. Here, using satellite-based maps and secondary data, we quantify the direct deforestation and forest degradation between 2000 and 2019 in the entire cocoa-growing region of Ghana which is attributed to the land uses (LUs) detected in 2019. Then, we use a land-balance approach to assess the indirect role of the expansion of LUs in deforestation and degradation for food crops. We find that cocoa was the major direct driver over that period (∼57%), followed by food crops and logging (∼39% in total), then by mining (3%), tree plantations (2%) and settlements (<1%). Roughly 30% of the deforestation and degradation of land used for food crops in 2019 was attributed to their displacement from elsewhere by other LUs—with 15% (9%–17%) due to cocoa expansion into food crops. In cocoa-saturated regions, indirect deforestation is likely to increase as forests only remain in gazetted areas, where growing food crops is either legal or more tolerated by officials than cocoa. Accounting for its direct and indirect role, cocoa was associated with ∼20% of the deforestation in gazetted areas. This research highlights the need to move away from sustainability efforts targeting one single commodity at a time to more transformative approaches that develop a coordinated vision across the food and land system. Such a vision would regulate multiple commodities holistically, address lock-ins, and reconsider the overall use of land systems in the region (how much land should be dedicated to cocoa, how and for whose benefits).